Neuroimmune pathways involvement in neurodegeneration of R6/2 mouse model of Huntington’s disease - Paldino, Emanuela; Migliorato, Giorgia; Fusco, Francesca R. (Frontiers in Cellular Neuroscience, 2024)
Mechanisms of tissue damage in Huntington's disease (HD) involve excitotoxicity, mitochondrial damage, and neuroinflammation, including microglia activation. CD47 is a membrane protein that interacts with the inhibitory immunoreceptor SIRPα. Engagement of SIRPα by CD47 provides a downregulatory signal that inhibits host cell phagocytosis, promoting a "don't-eat-me" signal (Elward K et al., 2003). These proteins are involved in the immune response and are downmodulated in inflammatory diseases. The involvement of inflammation and of the inflammasome in HD has already been described (Paldino et al.,2020). In this study, we focused on other factors that can be involved in the unregulated inflammatory response that accelerates and exacerbate the neurodegenerative process in HD. Our results show that CD47 on striatal neurons decreased in HD mice, while it increased in wild type mice with age. SIRPα, on the other hand, was present in neurons in the wild type and increases in the R6/2 mice at all stages. Recruitment of SIRPα and binding to CD47 promotes the activation through phosphorylating events of non-receptor protein tyrosine phosphatase SHP-1 and SHP-2 in neurons and microglia. SHP phosphatases are able to curb the activity of NLRP3 inflammasome (Guo W et al.,2017) thereby reducing the detrimental effect of neuroinflammation. Such activity is mediated by the inhibition (dephosphorylation) of the proteins signal transducer and activator of transcription (STAT). We found that activated SHP-1 was present in microglia and neurons of WT mice at 5 and 13 weeks, increasing with time; while in R6/2 it was not localized in neurons but only in microglia, where it decreases with time. Consequently, STAT1 was overexpressed in neurons of R6/2 mice, as an effect of lack of modulation by SHP-1. Thus, our results shed light on the pathophysiology of neuronal damage, on one hand, paving the way towards a modulation of signal transducer proteins by specific inhibitors to achieve neuroprotection in HD, on the other.